Oxford handbook of political psychology - Huddy, Leonie; Jervis, Robert; Sears, David O. (Oxford University Press, 2003)
This book is the third in a series of handbooks sponsored by the International Society of Political Psychology, following the Handbook of Political Psychology (1973) and Political Psychology: Contemporary Problems and Issues (1986). The authors and editors are distinguished international political scientists, psychologists, and sociologists. In sum, the editors have organized a wide-ranging reference work, with generally helpful literature reviews, although some authors focus on their own research programs. Mostly the chapters tend to be stronger on descriptive reviews of literatures than on sharply identifying gaps in knowledge and providing directions for specific future research, although some chapters do a nice job of laying out future research agendas. Some chapters also seem to give equal weight to studies with strong and weak research designs. The volume is not entirely successful in bridging the elite/mass divide in studies of political psychology (see, however, the effort by McGraw in chapter 12, as well as that of Klandermans in chapter 19). Certainly more needs to be said in political psychology about the interaction of elites and masses, such as the collective or aggregate consequences of individual beliefs and opinions, or the consequences of elite actions for publics. Common themes include the role of threat in producing psychological effects among both elite and mass as well as the need to bring together emotion and cognition in explaining political behavior. Clearly there remains much to be done in political psychology, although the scope of research done thus far is impressive.